ANALYSIS OF TOURISM SUSTAINABILITY IN CISANGKU CONSERVATION VILLAGE USING A MULTIDIMENSIONAL APPROACH - Andik Purwoko; Nurhayati; Hadi Susilo Arifin (RADJA PUBLIKA, 2026)
Conservation-based tourism is a strategic approach to sustainable development because it integrates economic, social, and environmental aspects. Cisangku Conservation Village in Malasari Village, Bogor Halimun Salak Geopark Area, has the potential to become a sustainable tourism destination based on conservation and community empowerment, although it still faces various management challenges. This study aims to analyze the level of tourism sustainability in Cisangku Conservation Village multidimensionally. The method used is Multidimensional Scaling (MDS) through the RAP-Tourism tool with five dimensions of sustainability: ecology, economy, social, infrastructure, and institutions. Data were obtained through field observations, questionnaires with 100 tourists, and interviews with key informants selected purposively. Sensitivity analysis was used to identify the attributes that most influence sustainability. The results showed that the tourism sustainability index of Cisangku Conservation Village was 68.53, which is categorized as moderately sustainable. The social dimension is categorized as highly sustainable, while the other dimensions are categorized as moderately sustainable. In conclusion, tourism sustainability in Cisangku Conservation Village is determined by the integration of environmental management, community participation, infrastructure support, and strengthening local institutions.